Ergonomic postural knowledge and perceived anatomical pain among dental students in Peru: a cross-sectional study - Thais Brighitte Acosta-Oliveros; Anali Gamboa-Dominguez (TUMI Oral Health, 2026)
Introduction: Dental students are frequently exposed to prolonged clinical postures that may contribute to musculoskeletal discomfort. Adequate knowledge of ergonomic principles is therefore relevant during professional training. Objective: To determine the relationship between knowledge of ergonomic working posture and perceived anatomical pain among dental students at a Peruvian university. Methods: An observational cross-sectional study was conducted among 86 dental students from the fifth to ninth academic cycles in Trujillo, Peru, selected by simple random sampling. Data were collected using an online questionnaire that assessed ergonomic postural knowledge and perceived anatomical pain. Knowledge was classified as low, moderate, or high, whereas pain intensity was categorized as mild, moderate, intense, or very intense. Absolute and relative frequencies were calculated, and the association between variables was evaluated using Pearson’s chi-square test. Results: Moderate ergonomic postural knowledge was the most frequent category (67.4%, n = 58), followed by high (20.9%, n = 18) and low knowledge (11.6%, n = 10). Mild anatomical pain was reported by 73.3% (n = 63) of students, moderate pain by 24.4% (n = 21), and intense pain by 2.3% (n = 2); no participant reported very intense pain. A statistically significant association was identified between ergonomic postural knowledge and perceived anatomical pain (χ² = 16.403; p < 0.001). Conclusions: Ergonomic postural knowledge was significantly associated with perceived anatomical pain among dental students, supporting the importance of strengthening ergonomic education during clinical training.